Enseñanza de español como segunda lengua para adultos mayores: algunas consideraciones. - Alvarado Cantero, Lucía (2012)
This article reviews previous investigations that relate teaching a second language with the age of learners, particularly those studies that analyze the learning differences at different ages. Furthermore, it presents the variables that must be considered in a pragmatic teaching of the language for persons at an elderly age.